Peningkatan Kemampuan Penalaran Matematika Siswa Melalui Model Pembelajaran Group Investigation(GI) (PTK Pembelajaran Matematika Kelas XI Tata Busana (TB) di SMK Muhammadiyah Kartasura Tahun Ajaran 2014/2015) - Erawati, Erna, Dra. Nining Setyaningsih, M.Si (2015)
ABSTRACT Erna Erawati/A410112005. The Improvement Of Students' Reasoning Ability Skills By Applying Group Investigation Model (CAR Mathematics Learning Grade XI Tata Busana (TB) of Muhammadiyah Vocational High School of Kartasura year 2014/2015). Thesis. Education In Mathematics Departement, Faculty Of Teacher Training And Education. Muhammadiyah University Of Surakarta. Juni,2015. The purpose of this research is to describe the improvement of students' reasoning ability skills by applying Group Investigation Model. This research is a Classroom Action Research (CAR). The subject that receive the action is grade XI TB of Muhammadiyah Vocational High School of Kartasura. The number of students of grade XI TB are 10 students. The data collection techniques are observation, field notes, test and documentation. The technique of data analysis is qualitative descriptive. Based on the research analysis it can be concluded that the application of Group Investigation Model can improve student's reasoning ability skills of student grade XI TB. It can be seen from the increase in the precentage of indicators reasoning ability skills, namely (1) showing conjectures from 10% increase to 70%, ( 2) manipulating mathematics as much as 20% increase to 80%, (3) providing grounds for their answer as much as 0% increase to 60%, (4) drawing conclution of mathematical problem increased as much as 20% to 60%.